Uporaba avtentičnih besedil pri predavanjih in vajah iz tujega strokovnega jezika na tehniških fakultetah - Mulej, Sabina (Vestnik za tuje jezike, 2014)
A high level of reading literacy is required for successful studies. Unfortunately, the surveys show that it has become worse at all study levels. In foreign language lectures and seminars, we want to improve it by occasional work with authentic materials such as technical articles. Such materials are convenient for bigger as well as for smaller student groups and are authentic. They encourage linguistic, practical and cognitive skills, creative thinking, cooperation among students and productive team work. By working with technical articles, students gain language and discipline-related knowledge. This kind of approach is student-centred, the role of the language teacher is changed; he/she is more of an observer, listener and facilitator than lecturer. The articles can be dealt with in many ways, using different strategies. Applying authentic materials is a relatively easy and convenient way of improving not only your students' discipline-related knowledge and skills but also their confidence in a real situation.
Keywords: tuji jeziki; strokovni jezik; avtentična besedila; učne strategije; jezikovne zmožnosti; tehniške fakultete; jezikovne kompetence